Victorian Alpine Plot Network (Alpine Summit Plots): Plot Spatial Details for Lowland-to-highland Roadside Transects Data, South-East Highlands, Australia - John Morgan (TERN Australia, 2014)
This Victorian Alpine Plot Network Road Transects Data Package comprises transect-based vegetation data for Lowland-to-highland Roadside Transects in the South-East Highlands, Australia. These data have been used against background quadrat data to test a hypothesis about roads as vectors for dispersal of invasive species. Plots are located at attitudinally stratified intervals along five attitudinally-stratified transects. The transects follow major roads and management tracks in the Victorian Alps. Each road is divided into 20 altitudinal sectors in which a single plot is situated. Within each plot, all species are identified and are assigned cover scores. The Alpine Summit plots study, which commenced in 2001, forms part of the collection of data packages by the Victorian Alpine Plot Network. A synopsis of related data packages which have been collected as part of the Victorian Alpine Plot Network’s full program is provided at http://www.ltern.org.au/index.php/ltern-plot-networks/victorian-alpine.